Contribution à l’étude biochimique et microbiologique des coproduits de la mer : cas du thon rouge Thunnus thynnus (Linné, 1758) - HADDOU, Fairouz; BESSEGHIR, Djamila (My University, 2017)
In recent decades, the excess demand for bluefin tuna in the Mediterranean , has created a problem of waste dumping (co-produced) in different environments, which accentuates pollution. So our job is to enhance co-products in the field of microbiology, In order to use them as a source of proteins composing culture media for microorganisms. We then studied the possibility of using tuna by-products as a source of bacteria of industrial interest, including lactic acid bacteria. From the results obtained through biochemical analyzes, it has been found that the tuna waste powder (fish meal) and the obtained protein isolate have a high biological value followed by chemical hydrolysates with biochemical characteristics which are not negligible. The results of preparation of the culture media confirmed the same biochemical results: The two products (powder and protein isolate) can replace the basic elements in the preparation of culture media for microbiology and bacterial and fungal growth.
Keywords: bluefin tuna; Thunnus thynnus; co-produced; valorisation; hydrolysates; microbiology; thon rouge; Thunnus thynnus; coproduit; valorisation; hydrolysats; microbiologie